The Influence of Health Education on Increasing Self Awareness of Coronary Heart Disease Prevention in High Risk Population - Rahmania Ambarika; Indah Aprilia Angelina (Journal Of Nursing Practice, 2025)
Background: Coronary heart disease is one of the leading causes of death in Indonesia. Ideally, people should understand the basic signs, symptoms, and early prevention of coronary heart disease. However, in reality, many people are still unaware, leading to a lack of self-awareness regarding the prevention of coronary heart disease. Purpose: The aim of this study is to analyze the effectof health education on increasing self-awareness for the prevention of coronary heart disease inhigh-riskpatients. Methods: This study uses a pre-experimental approach with a one-group pre-test and post- test design and an accidental sampling technique involving 49 respondents of high risk populations. The research instrument was a questionnaire and giving health education for increasing the self awareness. Results: The results of the study showed that before the health education, most respondents had moderate self-awareness with a prevalence of 69.39%, amounting to 34 respondents. After the health education, self-awareness improved significantly, with almost all respondents exhibiting good self-awareness with a prevalence of 77.52%, totaling 38 respondents. The Wilcoxon sign rank test getting a result p value  0.00, indicating that health education had a significant effect on increasing self-awareness. Conclusion: This health education can enhance self-awareness as it provides knowledge on how to prevent coronary heart disease. With this information, individuals better understand the importance of preventive measures and become more aware of their own condition, thus encouraging better behaviors in maintaining heart health.